1996
DOI: 10.1113/expphysiol.1996.sp003993
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an anion conductance and beta‐cell depolarization during hypotonically induced insulin release

Abstract: SUMMARYThe perforated patch technique was used to study the effects of hypotonic extracellular solutions on membrane potential and whole-cell currents in intact rat pancreatic ,l-cells. A 30 % reduction in osmolarity resulted in activation of an outwardly rectifying CF-selective conductance in rat f-cells. This conductance was inhibited by the anion channel blocker 4,4'-diisothiocyanatostilbene-2,2'-disulphonic acid (DIDS). Exposure to a hypotonic medium also led to a transient stimulation of electrical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 9 publications
(28 reference statements)
10
84
2
Order By: Relevance
“…The increase in cell volume observed following the addition of n-octanol under isotonic conditions has not previously been recorded with other VRAC inhibitors. We suggest that this phenomenon reflects the high effectiveness of n-octanol as a VRAC inhibitor, and is consistent with the suggestion that the conductance in b-cells is active even under isosmotic conditions [7].…”
Section: Octanoic (Caprylic ) Acidsupporting
confidence: 72%
“…The increase in cell volume observed following the addition of n-octanol under isotonic conditions has not previously been recorded with other VRAC inhibitors. We suggest that this phenomenon reflects the high effectiveness of n-octanol as a VRAC inhibitor, and is consistent with the suggestion that the conductance in b-cells is active even under isosmotic conditions [7].…”
Section: Octanoic (Caprylic ) Acidsupporting
confidence: 72%
“…1). The pattern of this inward current closely resembled that previously shown to accompany hypotonically induced cell swelling (Best et al 1996). In accordance with this, methylglyoxal activated an outwardly rectifying conductance in voltage-pulse experiments using Cs + -rich solutions.…”
supporting
confidence: 65%
“…In accordance with this, methylglyoxal activated an outwardly rectifying conductance in voltage-pulse experiments using Cs + -rich solutions. This conductance was virtually identical to the volume-sensitive anion conductance activated by exposure to hypotonic solutions (Best et al 1996). The application of 1 mmol 1-1 methylglyoxal to single rat ,8 -cells resulted in an increase in cell volume to a relative value of 1' 33 ± 0'03 (mean ± S.E.M., n = 4) after 10 min of exposure.…”
mentioning
confidence: 54%
“…5B). In a previous study, 100 mol/l DIDS was found to block 67% of hypotonically induced insulin release from rat islets (38). In contrast, hypotonically induced secretion was unaffected by 100 mol/l niflumic acid, even though niflumic acid was found to be a more effective blocker of I Cl,islet (P Ͻ 0.05) (compare Fig.…”
Section: Resultsmentioning
confidence: 89%
“…3A), followed by a spontaneous regulatory volume decrease (RVD). RVDs have been observed previously after the application of hypotonic solutions to rat ␤-cells (36,37), RINm5F cells (38), and mouse ␤-cells (39). When the hypotonic solution also contained 100 mol/l niflumic acid, the RVD was largely blocked, and cell volume increased significantly by an additional 29.5% over that observed when hypotonic solution alone was applied (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%